Pengaruh Karakteristik Anggaran Terhadap Efisiensi Biaya - Badrih, Badrih; Prastiwi, Arum (TEMA, 2006)
In the fast changing business environment, the budget constitutes a very important component. Instead of being a controlling tool, budget also becomes those of coordinating, communicating, motivating and evaluating the achievement. In relative with the importance of company ’s budget, the budget must be prepared cautiously. Kennis (1979) asserts that the budget has characteristics, (1) budget preparation participation, (2) budget objective clarity, (3) budget feedback, (4) budget evaluation, and (5) budget difficulty rate. Research attempts to examine the Effect of Budgetary Characteristic on Work Achievement. Throughout 28 departmental managers as respondent, results of research indicate that budgetary participation, budget objective clarity, budget difficulty rate and budgetary feedback, have significant positive effect on managerial work achievement in the observed companies. Budgetary evaluation has significant negative effect. Regression line effectiveness explains the variance of work achievement variable in the company for 60.7 %. The remaining variation of 39.3 % doesn’t come into model’s consideration. The finding of regression analysis contributes to the previous research findings. Keywords: Budget preparation participation, budget objective clarity, budgetfeedback, budget evaluation, budget difficulty rate, work achievement.